Competence approach – teaching the theory of modern foreign language education - Aнипинa, A. К.; Шәріпқaзы, Н. (Journal of Oriental Studies, 2017)
Recently, the concept of pedagogy widely studied competence. Highly qualification specialists started to wonder the meaning of competence, they began to engage in research on this field. In this regard, this article discusses the following use of the competency approach, determined by the importance of this method. In addition, the identified features of the competency training, four aspects of the use of competency approach were shown.